Forecasting the performance and profitability of companies using the equation of Tobin’sq (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The main objective and primary concern to every investor not only to achieve a greater return on his or her investments, but also to create the largest possible value of these investments the, researchers and those interested in the field of investment and financial analysis  try to develop standards  for performance      valuation      is guided through the                                                    investor decision-making  a    sound investment                                       and direct investment to maximize his wealth ,   in this sense appeared measures concerned with the assessment internal evaluation such as (ROI), (ROA) and others that reflect the point of view in the evaluation of  the management performance, and other measures that are interested in assessing the market for investments such as (EPS), Dividends per share (DPS),( P / E)), (market value to book value) (mv / bv) what is known as the accounting or traditional standards , and then were developed modern standards concerned with the market evaluation to assess the performance and profitability of companies, including (MVA), ( EVA) , ( Tobin'sq) ) that guide the investor in making sound decisions, and we will focus in this study, on the proportion of ( Tobin'sq) as the standards of modern that the  researcher believes according to his knowledge, lack of interest by the Arab investor in general and the Iraqi investors in particular in guiding the investment decision to invest in Common Stock  traded on the Iraq Stock Exchange.